Photo-induced morphological winding and unwinding motion of nanoscrolls composed of niobate nanosheets with a polyfluoroalkyl azobenzene derivative. Issue 24 (7th June 2016) - Nabetani, Yu; Takamura, Hazuki; Uchikoshi, Akino; Hassan, Syed Zahid; Shimada, Tetsuya; Takagi, Shinsuke; Tachibana, Hiroshi; Masui, Dai; Tong, Zhiwei; Inoue, Haruo
Abstract : Photo-responsive nanoscrolls of niobate nanosheets show a giant morphological motion. Abstract : Photo-responsive nanoscrolls can be successfully fabricated by mixing a polyfluoroalkyl azobenzene derivative and a niobate nanosheet, which is exfoliated from potassium hexaniobate. In this study, we have found that the photo-responsive nanoscroll shows a morphological motion of winding and unwinding, which is basically due to the nanosheet sliding within the nanoscroll, by efficient photo-isomerization reactions of the intercalated azobenzene in addition to the interlayer distance change of the nanoscrolls. The relative nanosheet sliding of the nanoscroll is estimated to be ca . 280 nm from the AFM morphology analysis. The distance of the sliding motion is over 20 times that of the averaged nanosheet sliding in the azobenzene/niobate hybrid film reported previously. Photo-responsive nanoscrolls can be expected to be novel photo-activated actuators and artificial muscle model materials.